(untitled) (Práxis Educativa, 2023)
This work discusses the Agroecology potential as a point of confluence and mobilization between different knowledge and practices in different educational contexts, especially in teaching degrees. For this, it starts from the analysis of a pedagogical event involving different undergraduate classes in different qualifications: Biological Sciences and Rural Education in Natural Sciences and in Languages and Codes. From a theoretical point of view, it is proposed the exercise of articulating references from different scientific communities, focusing on prioritizing dialogic and ecological postures. The reflections presented aim to contribute to a broader debate on emancipatory, sustainable and cooperative pedagogical practices, which are understood here as important in citizenship education both in rural and urban schools. Keywords: Agroecology. Ecology of practices. Dialogic education.